The Mapping of Local Wisdom Found in the Lara Pangkon’s Speech in the Wedding Reception of Ngantang People - Fitriani, Enis; Ifianti, Trisnian (Universitas Nahdlatul Ulama Blitar, 2023)
The purpose of this research was to map the local wisdom that appears in the customary speech of lara pangkon in the wedding reception of Ngantang people. The researchers found there are 32 meanings of expectation in the local wisdom of meaning, 4 meanings of affection in the local wisdom of meaning, 3 meanings of advice in the local wisdom of meaning, 18 functions of cultural symbol in the local wisdom of function, and 1 cultural value in the local wisdom of value. The meanings of expectation, affection, and advice in the local wisdom of meaning found refer to the changing mindsets and social relations between individuals and groups by creating a common meeting point, the cultural symbol functions in the local wisdom of function in lara pangkon‘s speech refer to a symbol of cultural diversity for a community, and the cultural value refers to cultural elements that grow from the bottom up, and form organically in society. Exploring qualitative investigations, investigating the cross-cultural applicability of cultural symbols' functions as unifying agents, and examining the natural emergence of cultural values have the potential to enhance our comprehension of local wisdom's dynamics and its tangible impacts on community resilience and unity.